Development of mean-line model of a turbocharger [electronic resource] - Khairul Azlan Ariffin, 1985- (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal-Automotif)) - Universiti Teknologi Malaysia, 2008